Flower power: its association to bee power and floral functional morphology in papilionate legumes - Córdoba, Silvina Alejandra (2011)
Background and Aims A test was made of the hypothesis that papilionate legume flowers filter pollinators according to their ability to exert strength to open flowers to access rewards. In addition, interactions with pollen vectors were expected to explain the structural complexity of the architecture of these flowers since operative flower strength may be determined by a combination of morphological traits which form part of an intrafloral functional module. Methods Six papilionate species were studied:Collaea argentina, Desmodium uncinatum, Galactia latisiliqua, Lathyrus odoratus,Spartium junceumandTipuana tipu. Measurements were made of the strength needed to open keels and the strength that pollinators were capable of exerting. Morphological traits of all petals were also measured to determine which of them could be either mutually correlated or correlated with operative strength and moment of strength and participated in a functional module. Key Results It was observed that pollinators were capable in all cases of exerting forces higher and often several times higher than that needed to access floral rewards, and no association could be detected between floral operative strength and strength exerted by the corresponding pollinators. On the other hand, strong and significant correlations were found among morphometric traits and, of these, with operative strength and moment. This was particularly evident among traits of the keel and the wings, presumably involved in the functioning of the floral moveable mechanism. Conclusions Though visitors are often many times stronger than the operative strength of the flowers they pollinate, exceptionally weak bees such as Apis mellifera cannot open the strongest flowers. On the other hand, strong correlations among certain petal morphometric traits ( particularly between the keel and wings) give support to the idea that an intrafloral module is associated with the functioning of the mechanism of these legume flowers. In addition, the highly significant correlations found across petals support the view of functional phenotypic integration transcending the ontogenetic organization of flower structure. Key words:Fabaceae, legume, papilionate flowers, pollination, biomechanic, filtering mechanism, floral phenotypic integration, bee, strength, functional module.